Theoretical Analysis and Experimental Research of Spindle Swing Compound Barrel Finishing - Ding Xiongxiong; Zhang Yan; Li Wenhui; Li Xiuhong (Jixie chuandong)
A spindle swing compound barrel finishing equipment for gear machining is proposed. The calculation model of cutting speed and cutting angle is established. The influence of various parameters on cutting speed and cutting angle is analyzed by using Matlab software. The rationality of the design of spindle swing compound barrel finishing equipment is theoretically verified. An experimental device with adjustable parameters is developed. Machining experiments shows that the surface roughness Ra decreased from about 0.8 μm to about 0.3 μm. The cutting trace is removed and the surface texture is the same. The result shows that the equipment can effectively improve the surface quality of gears and obtain the uniform surface of gears.